دور لجنة البنود التعسفية في حماية المستهلك من التعسف: دراسة مقارنة بين القانون الفرنسي والجزائري - صوالح, محمد اعماره; جبارة نورة, نورة (University of Eloued جامعة الوادي, 2021)
لقد ساهم التزايد الكبير للتعامل بالعقود النموذجية وعقود الإذعان، في تكوين بيئة خصبة لفرض الشروط التعسفية في عقود الاستهلاك، حيث تُطرح في الغالب تلك العقود في شكل نماذج معدَّة مسبقًا بشكل انفرادي من قبل المتدخل، وبسبب التفوق الاقتصادي والقانوني له فإن المستهلك لا يستطيع رفضها أو مناقشتها، ومن ثم فإنه يجب توفير الحماية اللازمة لهذا الأخير كطرف ضعيف وتحقيق التوازن العقدي بينه وبين المتدخل. كما سعت أغلب التشريعات الحديثة إلى مكافحة التعسف في العقود من خلال استخدام نظام قوائم الشروط المحظورة، كما استحدثت لجنة البنود التعسفية كهيئة إدارية استشارية، تقوم بالبحث عن الشروط التعسفية في نماذج العقود فتقترح تعديلها أو حذفها، كما تساعد جميع الفاعلين في هذا السياق بداية بالإدارة المعنية والقضاء وجمعيات حماية المستهلك، عن طريق إبداء آراء وصياغة توصيات غير ملزمة لهم إلا إذا تم تطبيقها بموجب مرسوم. Abstract: The great increase in dealing with model contracts and adhesion contracts has contributed to the formation of a fertile environment for imposing abusive Clauses in consumption contracts, as these contracts are often presented in the form of pre-prepared models unilaterally by the interlocutor, and because of his economic and legal superiority, the consumer cannot reject or discuss them. Therefore, the latter must be provided with the necessary protection as a weak party and a nodal balance must be achieved between it and the interfering. Most of the modern legislations have sought to fight against contracts' abusiveness by using the System of Prohibited Clauses Lists. The Abusive Terms Commission has been also created as an advisory management body that searches for the Abusive Clauses in contract forms and suggests to amend or delete them, In this context, it also helps all actors, beginning with the concerned administrations, the judiciary and consumer protection associations, by giving opinions and Drafting Recommendations that are not binding on them unless they are implemented by decree.
The Role of the Abusive Terms Commission in Consumer Protection from Abuse: A comparative study between French and Algerian law
مقال
Keywords: عقود الإذعان؛ الشروط التعسفية؛ لجنة البنود التعسفية؛ تقديم الاقتراحات؛ صياغة التوصيات.; Adhesion Contracts; Abusive Clauses; Abusive Terms Commission; Make suggestions; Drafting Recommendations.